Influencia de la música en el desarrollo socio-afectivo de los niños y niñas de educación inicial de la Escuela Fiscal Mixta Cleopatra Fernández de Castillo de la ciudad de Machala en el período 2011-201 - Suárez Brito, Sara Elizabeth (2013)
This research project consists of an organized and sequential set of useful to understand the influence of music on the socio-emotional development of children in early education stage school Cleopatra Fernandez de Castillo musical activities.